Implementasi Model Pembelajaran STEM Tipe Index Card Match Terhadap Keterampilan Berpikir Kritis Pada Materi Alat-Alat Optik - Fakhira Nursabrina; Wahyu Dian Laksanawati (Universitas Mandiri, 2023)
This study aims to implement the Index Card Match type STEM learning model for critical thinking skills in the material of optical devices. This research was conducted in the even semester of the 2021-2022 school year. The method used in this study is a Pre-Experimental Design with the type of research One-Group Pretest-Posttest Design. The population in this study were students in class XI MIPA 5 at SMAN 6 Tangerang Regency. The sampling technique used is Cluster Random Sampling. The data collected is based on the results of the Pretest, Posttest, and student learning activities which are arranged based on indicators of critical thinking, namely: (1) formulating problems; (2) giving arguments; (3) making deductions; (4) perform induction; (5) do evaluation. Then the data were analyzed using the t-test. The results of the hypothesis test obtained tcount = 3.7735 and ttable = 2.0645. Because tcount > ttable, there is an influence on the Index Card Match Type STEM learning model. And also, the activity of students increased during the three meetings. It can be said that after going through the calculation process at the 1st meeting, the percentages for each aspect were 45%, 34%, 39%, and 39%. At the 2nd meeting, the percentages were 60%, 57%, 51%, and 56%. At the 3rd meeting, the percentages were 71%, 72%, 75%, and 78%. Therefore, it can be said that the activity of students increased. So. It can be concluded that there is an increase in critical thinking skills by implementing STEM learning of the Index Card Match type in Optical Equipment material.